The Application of Problem-Based Learning (PBL) Accompanied by Crossword Puzzle to Improve The Activity and Learning Outcomes of Physics Students - Nila Dewi, Niken; subiki, subiki; Meilina, Ike Lusi (JURNAL PEMBELAJARAN FISIKA, 2025)
The prevailing pedagogical approach in class X SMA entails the utilization of questions from LKS or books, thereby engendering suboptimal student engagement and learning outcomes in physics.This study posits the necessity for pedagogues to enhance their lesson planning and media utilization in the classroom, with the objective of facilitating innovative Problem Based Learning (PBL) models accompanied by crossword puzzles.The present study aims to elucidate the enhancement of activity and learning outcomes of X grade high school students through the implementation of the PBL model accompanied by crossword puzzle media. The subject of this research is class X 2 SMAN 5 Jember.This research employed a Classroom Action Research approach, which was conducted in two cycles, each comprising four stages: planning, implementation, observation, and reflection.The results of the first cycle were used as a reference for the implementation of the second cycle, with improvements made to address the weaknesses identified in the first cycle. The findings of this study revealed that the implementation of the PBL model, coupled with the incorporation of a crossword puzzle, resulted in a 0.60 increase in student learning outcomes in cycle 1. Subsequent to cycle 2, there was an augmentation in the average student learning outcomes to 0.76 Furthermore, the analysis of learning activities in cycle 1 revealed an active category, while cycle 2 exhibited an increase, including an increase in the very active category. Consequently, it can be deduced that the implementation of the PBL model, integrated with a crossword puzzle, has led to a twofold enhancement in the activity and learning outcomes of physics students at SMAN 5 Jember.